2012
DOI: 10.1111/j.1471-4159.2012.07758.x
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Parla‐ and Parlb‐deficiency affects dopaminergic neuron patterning and embryonic survival

Abstract: Many genes associated with familial Parkinson's disease contribute to mitochondrial morphology and function. Some of these genes, for example, Pink1 and Parkin, are part of a common pathway. The presenilin-associated rhomboid-like (PARL) gene was recently linked to familial Parkinson's disease. The PARL gene product is found in the inner mitochondrial membrane and cleaves the optic atrophy 1 protein, involved in mitochondrial morphology and apoptosis. In Drosophila, the PARL-related rhomboid-7 gene acts upstre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…PARL is a component of the mitochondrial membrane involved in mitochondrial morphology and apoptosis. Morpholino knockdown of both zebrafish paralogs, parla and parlb , results in high mortality, whereas loss of PARLb leads to the mildest phenotype ( 94 ). Loss of one of the PARL’s results in mild neurodegeneration and disarranged dopaminergic neurons.…”
Section: Zebrafish As a Model Of Hypokinetic Movement Disordersmentioning
confidence: 99%
“…PARL is a component of the mitochondrial membrane involved in mitochondrial morphology and apoptosis. Morpholino knockdown of both zebrafish paralogs, parla and parlb , results in high mortality, whereas loss of PARLb leads to the mildest phenotype ( 94 ). Loss of one of the PARL’s results in mild neurodegeneration and disarranged dopaminergic neurons.…”
Section: Zebrafish As a Model Of Hypokinetic Movement Disordersmentioning
confidence: 99%
“…Moreover, PARL cleaves the optic atrophy 1 protein (OPA1) [94] that is a crucial protein involved in the fusion of inner mitochondrial membranes and in the formation of cristae , crucial for proper mitochondrial metabolism in early development [71]. Bioinformatics analyses revealed that in zebrafish there are two paralogues, parla and parlb , whose transcripts are both ubiquitously expressed during embryogenesis [63]. The PD-phenotype caused by the KD of both parl genes can be rescued by the overexpression of human PARL mRNA.…”
Section: Modeling Mitochondrial Defects In Zebrafishmentioning
confidence: 99%
“…Two PARL orthologues have been identified in the zebrafish: parla and parlb [15]. Both parl transcripts are expressed during embryonic development and in adult tissues.…”
Section: Parl In Zebrafishmentioning
confidence: 99%
“…Both parl transcripts are expressed during embryonic development and in adult tissues. Morpholinomediated knockdown of parla and parlb simultaneously causes embryonic lethality, increased acridine orange staining, and altered expression of tyrosin hydroxylase mRNA and dopamine transporter [15], which were used as markers of dopaminergic neurons. Interestingly, overexpression of zebrafish pink1, but not kinase dead pink1 or pink1 containing Parkinson' s disease causing mutations, rescues larval lethality or dopaminergic neurons abnormalities, indicating that parl is genetically upstream of pink1, confirming this pathway in vertebrates.…”
Section: Parl In Zebrafishmentioning
confidence: 99%